Developing Students’ Critical Thinking through Problem-Based Learning in English Class at SMK Putera Puteri Cendekia - Kurniawati, Elis; Ruqaiyah, Ruqaiyah (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study explores the implementation of Problem-Based Learning (PBL) in English language teaching and its contribution to developing students’ critical thinking skills at SMK Putera Puteri Cendekia. As vocational education increasingly emphasizes 21st-century competencies, critical thinking has become essential for preparing students to face real-world challenges. PBL provides a student-centered approach where learners engage with contextual problems through inquiry, group collaboration, and reflection. This research employed a qualitative descriptive method, involving one English teacher and Grade XI students. Data were collected through classroom observations, interviews, and field notes to capture the dynamics of PBL in practice. The results indicated that students actively participated in analyzing issues, constructing arguments, and presenting logical solutions. The teacher played a crucial role as a facilitator and co-investigator throughout the process. Despite several challenges, including limited time and varying English proficiency among students, the implementation of PBL fostered a supportive and engaging environment. Overall, PBL proved to be an effective strategy to enhance critical thinking in English language teaching within vocational school settings.